Systemic Candida parapsilosis Infection Model in Immunosuppressed ICR Mice and Assessing the Antifungal Efficiency of Fluconazole - Yu’e Wu; Fangui Min; Jinchun Pan; Jing Wang; Wen Yuan; Yu Zhang; Ren Huang; Lixin Zhang (Veterinary Medicine International)
This study was to establish a systemic C. parapsilosis infection model in immunosuppressed ICR mice induced by cyclophosphamide and evaluate the antifungal efficiency of fluconazole. Three experiments were set to confirm the optimal infectious dose of C. parapsilosis, outcomes of infectious model, and antifungal efficiency of fluconazole in vivo, respectively. In the first experiment, comparisons of survival proportions between different infectious doses treated groups showed that the optimal inoculum for C. parapsilosis was 0.9 × 105 CFU per mouse. The following experiment was set to observe the outcomes of infection at a dose of 0.9 × 105 CFU C. parapsilosis. Postmortem and histopathological examinations presented fugal-specific lesions in multiorgans, especially in kidneys, characterized by inflammation, numerous microabscesses, and fungal infiltration. The CFU counts were consistent with the histopathological changes in tissues. Th1/Th2 cytokine imbalance was observed with increases of proinflammatory cytokines and no responses of anti-inflammatory cytokines in sera and kidneys. In the last experiment, model based evaluation of fluconazole indicated that there were ideal antifungal activities for fluconazole at dosages of 10–50 mg/kg/d. Data demonstrates that the research team has established a systemic C. parapsilosis infection model in immunosuppressed ICR mice, affording opportunities for increasing our understanding of fungal pathogenesis and treatment.